Innovativeness and Entrepreneurial Success in Agricultural Sector: An Overview of the Literature in Developing Countries - Aloukoutou, Aline Modoukpè; Moussa, Ismaïl Moumouni (Journal of Agricultural Studies, 2024)
Business success is often attributed to the profile of the entrepreneur, the characteristics of the business and its environment. In most of developing countries, interventions to promote entrepreneurship are typically limited to the provision of finance and coaching to build business capital and management skills. These interventions have shown mixed results as only few young enterprises last more than five years, suggesting the need to explore other drivers of entrepreneurial success. This review adds a contribution on the role of innovation in the performance of agricultural enterprises through a synthesis of the existing literature on the importance of innovation in entrepreneurial success. Our results highlight that young agricultural entrepreneurs face several challenges, including the perception from their pairs/community, limited access to production resources, climate change, poor access to technologies and market, lack of management skills, and lack of appropriate policy support. Their innovativeness depends on their ability to mobilize livelihoods assets such as financial capital, social, human and symbolic capitals. Ultimately, innovativeness allows young entrepreneur to tap into livelihoods assets-related opportunities to ensure the competitiveness and further the success of their business. We also elaborated a framework to analyze entrepreneurial performance in the agricultural sector.